The Marketing for Vietnamese Dragon Fruit - Nguyen, Nguyen (Archives of Business Research, 2020)
The dragon fruit is a strong agricultural product of Vietnam, however, its market always faces the unstableness, and this situation can cause crisis and big damage for farmers. The paper studies the actual problems of product, and proposes marketing methods which aim to promote its sustainable development.